Editing the Soviet Sociological Journal: The Problem of Legitimacy in Soviet Sociology - Guba, Katerina (Journal of Economic Sociology, 2015)
In this article, we consider journals as organizations from neo-institutional organizational theory (W. Powell, P. DiMaggio, J. Meyer, and B. Rowan). An editorial office as an organization has to solve the problem of legitimacy. In the case of the Soviet journal “Sotsiologicheskiye issledovaniya” (“SotsIs”), the only specifically sociological journal in the USSR, it was done by matching journal headings to the official ideology of Soviet sociology. Drawing on an analysis of the journal headings for the Soviet period (1974–1991), I argue that structural divisions of the journal space reflected legitimate meanings of the Soviet sociology as a discipline which was created for increasing the ideological and administrative efficiency of the Soviet government. Journal categories were a signal of loyalty, which was required for the organization’s survival. During years of social and political changes, the role of the journal has changed. The journal has tried to attract general educated readers as well as visibly demonstrate this commitment to public issues by imitation of the evident features of ‘thick’ magazines and newspapers. In spite of all its changes, the journal has continued to depend on the meaning of sociology as a study of social problems. Externally given classifications have played a principal role in choosing an organizational form for searching and evaluating manuscripts. When the editorial office has clear tasks related to the content of the journal, the most appropriate form is the network form of governance because external reviewing makes it difficult to fill journal space. The organization has to use quasi-reviewing, which performs the function of bringing ‘raw’ manuscripts to contribute to the facade of the journal. The history of the Soviet “SotsIs” is a history of an organization, in which the content was tightly controlled, while control of the evaluation of manuscripts remained on the periphery.